Role of Combined Embolization and Ablation in Management of Renal Masses - Winokur, Ronald S.; Pua, Bradley B.; Madoff, David C. (Seminars in Interventional Radiology, 2014)
Combination of minimally invasive treatment modalities is being increasingly utilized to improve local tumor control and overall survival. In the liver, the combination of embolization and ablation results in equivalent overall survival and intrahepatic disease progression as surgical resection for lesions smaller than 7 cm. Ablation alone for small renal masses up to 4 cm results in excellent local tumor control and lack of residual enhancement to suggest viable tumor. A small number of studies have been performed combining embolization and ablation, which result in high rates of local tumor control for tumors smaller than 5 cm. Based on this small cohort, combined embolization and ablation may be most indicated for central or mixed tumors where ablation alone suffers from the greatest degree of “heat sink” effect. This article reviews the theory, methods, and outcomes of combining percutaneous ablative and embolic modalities in the treatment of renal masses.
Keywords: renal cancer; kidney cancer; embolization; ablation; combination therapy; interventional radiology